2020
DOI: 10.1021/acs.est.0c04889
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Exposure to Low Concentrations of Oil on the Expression of Cytochrome P4501a and Routine Swimming Speed of Atlantic Haddock (Melanogrammus aeglefinus) Larvae In Situ

Abstract: Exposure to environmentally relevant concentrations of oil could impact survival of fish larvae in situ through subtle effects on larval behavior. During the larval period, Atlantic haddock (Melanogrammus aeglefinus) are transported toward nursery grounds by ocean currents and active swimming, which can modify their drift route. Haddock larvae are sensitive to dispersed oil; however, whether exposure to oil during development impacts the ability of haddock larvae to swim in situ is unknown. Here, we exposed At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…These four parameter sets encompass a wide range of uncertainty in both threshold levels and effects for petroleum compounds (Carroll et al, 2018). For context, the lowest reported effect concentration for haddock is 10 μg/L of oil (0.1 μg/L ∑ PAH) (Cresci et al, 2020). For cod, the lowest nominal crude oil concentration is 140 μg/L (Nordtug et al, 2022).…”
Section: Haddock Codmentioning
confidence: 99%
See 1 more Smart Citation
“…These four parameter sets encompass a wide range of uncertainty in both threshold levels and effects for petroleum compounds (Carroll et al, 2018). For context, the lowest reported effect concentration for haddock is 10 μg/L of oil (0.1 μg/L ∑ PAH) (Cresci et al, 2020). For cod, the lowest nominal crude oil concentration is 140 μg/L (Nordtug et al, 2022).…”
Section: Haddock Codmentioning
confidence: 99%
“…Such studies have revealed effects that include cardiac function, cholesterol biosynthesis, peripheral and central nervous system function, the stress response, osmoregulatory acid-base balance processes and photo-induced toxic responses (Barron et al, 2004;Incardona et al, 2013Incardona et al, , 2015Roberts et al, 2017;Grosell and Pasparakis, 2021;Sørhus et al, 2021;Aranguren-Abadía et al, 2022). In the past decade, there has further been an increase in studies focused on behavioral responses to oil exposures and the transfer of toxic substances from parent to offspring (Incardona et al, 2015;Cresci et al, 2020;Bautista et al, 2020). These investigations aid efforts to identify and understand impacts on aquatic life and to support risk management procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Along with cardiotoxic effects, oil exposure has been found to increase the oxygen consumption rate of early life stages of warm‐ and cold‐water fishes (Cohen et al, 2001; Eldridge et al, 1977; Klinger et al, 2015; Pasparakis et al, 2016), which may allocate energy away from fitness‐related performance such as growth, development, foraging, and swim performance/predator avoidance (Incardona et al, 2014; Klinger et al, 2015; Laurel et al, 2019; Pasparakis et al, 2016). Exposure of embryonic and larval fishes to physically dispersed crude oil has been linked to concentration‐dependent increases in the incidence and severity of spinal curvatures (Khursigara et al, 2017; Nahrgang et al, 2016) and yolk‐sac edemas (Incardona et al, 2014; Laurel et al, 2019; Nahrgang et al, 2016) and decreases in swim performance (Cresci et al, 2020; Mager et al, 2014) and hatching success (Hansen et al, 2019; Laurel et al, 2019). Overall, environmentally relevant oil exposure appears to be highly detrimental to developing warm‐ and cold‐water fishes.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, functional and developmental heart abnormalities, jaw and abnormally shaped eyes and/or reduced eye size have been documented [1][2][3][4][5][6][7] . Later in life (juveniles and adult stages), these impairments may lead to increased injuries, developmental delays, changes in swimming capacity and mortality [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%